2014
DOI: 10.1090/noti1173
|View full text |Cite
|
Sign up to set email alerts
|

The Misfortunes of a Trio of Mathematicians Using Computer Algebra Systems. Can We Trust in Them?

Abstract: Computer algebra systems are a great help for mathematical research but sometimes unexpected errors in the software can also badly affect it. As an example, we show how we have detected an error of Mathematica computing determinants of matrices of integer numbers: not only it computes the determinants wrongly, but also it produces different results if one evaluates the same determinant twice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…It is an area of Mathematics perceived as the main source of failure in the undergraduate level because of its nature which involves abstract and complex ideas and the way it is being taught to the students (Sahin, Cavlazoglu & Zeytuncu, 2015). With these, initiatives around the world have introduced a range of innovative and interactive learning technologies such as graphic software (Robutti, 2010;Lavizca, 2010) and computer algebra system (Özgün-Koca, 2010;Mignotte, 2012;Durán, Pérez & Varona, 2014) to explore Calculus concepts. The use of these technologies offer new ways to learn and teach Calculus that help deepen students' understanding of abstract and complex ideas (Arango, Gaviria & Valencia, 2015;Šumonja, Veličković & Šubarević, 2015;Zakaria & Salleh, 2015) which include conceptual understanding (Bartell, Webel, Bowen & Dyson, 2013;Richland, Stigler & Holyoak, 2012) and procedural skills (Rittle-Johnson & Schneider, 2014;Cragg & Gilmore, 2014) and also increases positive attitude of students towards the subject (Sang, Valcke, Van Braak & Tondeur, 2010;Yuan & Chun-Yi, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is an area of Mathematics perceived as the main source of failure in the undergraduate level because of its nature which involves abstract and complex ideas and the way it is being taught to the students (Sahin, Cavlazoglu & Zeytuncu, 2015). With these, initiatives around the world have introduced a range of innovative and interactive learning technologies such as graphic software (Robutti, 2010;Lavizca, 2010) and computer algebra system (Özgün-Koca, 2010;Mignotte, 2012;Durán, Pérez & Varona, 2014) to explore Calculus concepts. The use of these technologies offer new ways to learn and teach Calculus that help deepen students' understanding of abstract and complex ideas (Arango, Gaviria & Valencia, 2015;Šumonja, Veličković & Šubarević, 2015;Zakaria & Salleh, 2015) which include conceptual understanding (Bartell, Webel, Bowen & Dyson, 2013;Richland, Stigler & Holyoak, 2012) and procedural skills (Rittle-Johnson & Schneider, 2014;Cragg & Gilmore, 2014) and also increases positive attitude of students towards the subject (Sang, Valcke, Van Braak & Tondeur, 2010;Yuan & Chun-Yi, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, they presented an example involving a 14 × 14 matrix of pseudorandom integers between −99 and 99, which was then multiplied by a certain diagonal matrix with large entries, and then added to another matrix of pseudorandom integers between −999 and 999. When they then attempted to compute the determinant of the resulting fixed matrix using Mathematica version 9, the found that the results were not consistent -they often obtained different answers for the same problem [27]. This problem now seems to have been resolved in Mathematica version 10, according to some tests by the present authors.…”
Section: Reproducibility In Symbolic Computingmentioning
confidence: 81%
“…Computer algebra systems, such as Mathematica and Maple, have also been used to solve differential equations symbolically and to overcome the inaccuracies introduced by computer arithmetic based computations and numerical methods. However, the algorithms used by these systems are not rigorously verified and thus can produce error-prone results [29]. These flaws in the traditional techniques are tremendously undesirable in case of the high safety-critical domain of transportation, as ignoring some corner cases may lead to dire consequences, such as frequent traffic congestions, road accidents and loss of human lives in worst cases.…”
Section: Related Workmentioning
confidence: 99%